PERSEPSI ANGGOTA TENTANG PROSEDUR PEMBERIAN KREDIT DI KOPERASI SERBA USAHA (KSU) REJOSARI PEKANBARU - Ilham, Annisa; Suarman, Suarman; Riadi, RM (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine members' perceptions about procedure for granting credit at KSU Rejosari. The research population was members Koperasi that make loans are with 264 people and The sample used was 53 people with random sampling techniques. This research uses primary data sourced from direct research to Koperasi Serba Usaha Rejosari Pekanbaru. The data analysis technique used is technical descriptive data analysis and use SPSS program (Statistical Product and Service Solutions). The results showed that the procedure for giving credit to KSURejosari is generally good but improvements are still needed.Key Words: Koperasi Serba Usaha, Member Perception, Procedure for Granting Credit